Quantitative hyperspectral analysis for characterization of the coastal water from Damietta to Port Said, Egypt - Islam Abou El-Magd (Egyptian Journal of Remote Sensing and Space Sciences, 2014)
The coastal zone of the Nile Delta is wealthy of natural resources that currently accommodate and support not less than one third of the population. However, it is still a promising area for energy resources and industrial activities that initiated the country to develop new action plans for industrial estates and services; it is under extreme environmental pressure. The newly developed techniques of remote sensing offer effective tool to monitor such environment on a near-real time basis at minimum in situ sampling. Detection of water quality conditions and parameters is one of the major advantages of hyperspectral remote sensing technologies; which has been widely used to assess water quality conditions of many open water mass and aquatic ecosystems. This research looked at characterization of the water quality using the different functions of in situ measurements of hyperspectral sensors in conjunction with water quality multi-probe sensor. The spectral behaviour of the water at the outlets is quite different from the other sampling sites of the coastal water. Turbidity was recorded at high level of 65 (NTU) and chlorophyll was up to 147 mg/l at the outlets, which were positively correlated with the hyperspectral curve of the spectroradiometer and Hyperion data. The archived Hyperion data showed some similarities and differences with the in situ data that were mostly due to the timing differences between both datasets; it, however, enabled for understanding of the hyperspectral application in water quality.